Pemberdayaan Organisasi Ekstrakurikuler PMR dalam Upaya Peningkatan Pola Makan Gizi Seimbang dengan Media ‘Isi Piringku’ - Rinayati Rinayati; Sri Wahyuning; Harsono Harsono; Cempaka Kumala Sari; Sugeng Santoso (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
"Isi Piringku" is a dietary guideline developed by the Ministry of Health of the Republic of Indonesia as part of a balanced nutrition campaign. Understanding this concept is particularly important for elementary school-aged children, as this is a critical period for physical growth, mental development, and the formation of healthy lifestyle habits. A balanced nutritional intake plays a vital role in improving learning concentration, supporting physical activity, and preventing various diseases caused by nutritional deficiencies or excesses. However, the dietary behavior of elementary school students remains far from balanced nutrition principles, with an average achievement of only 53.9%. Based on this condition, this Community Service Program (PkM) aimed to improve the knowledge, skills, and behavior of Youth Red Cross (PMR) members at SDN Krapyak in consuming food according to balanced nutrition guidelines using the “Isi Piringku” media. The activities carried out included obtaining permission, conducting socialization, training on the use of the “Isi Piringku” media, and providing ongoing mentoring. Through this program, it was expected that PMR members could become change agents and role models for their peers in implementing healthy and balanced eating habits. The results of the activity showed that the mentoring was successfully conducted. There was a significant improvement in the knowledge and skills of PMR members, as reflected in the increase in the average score from 70.8 to 90.97 after the intervention. This indicates that the approach using the "Isi Piringku" media is effective in promoting balanced nutritional behavior among elementary school children.